Тень смерти - Белоусов Владимир (Новый русский детектив, 1996)
Экземпляры: ф.7 (1996) / Инвентарный номер: 39119 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Б 43 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44